Optimalisasi Pendekatan Deep Learning untuk Meningkatkan Kualitas Pembelajaran Ekonomi dalam Kurikulum Merdeka di SMA Batik 2 Surakarta - Ayu Sogy Aprilia; Mutiara Pambayun (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study aims to analyze the implementation of the Independent Curriculum and the role of teachers as facilitators in the application of the deep learning approach to economics learning at SMA Batik 2 Surakarta. The research method uses a qualitative descriptive approach with observation techniques to determine the learning process of student involvement, as well as the effectiveness of teacher strategies. The results of this study reveal that the Lecture method used by the teacher results in students' understanding of economic concepts being superficial, which prevents them from achieving deep understanding. Teachers have not fully carried out their role as facilitators, particularly in terms of providing sparking questions, facilitating analytical discussions, and offering constructive feedback. Additionally, the lack of use of contextual learning resources prevents students from connecting economic concepts to real-world phenomena. This finding emphasizes the need for teachers to adopt more interactive teaching strategies, engage students in meaningful discussions, and integrate real-life examples into the learning process to enhance the depth of student understanding and the overall learning experience.